The Influence of Workplace Facilities and Work Environment on Employee Involvement with Self-Efficacy as an Intervening Variable (A Study at PT. Saprotan Utama Semarang) - Nuraziz, Rafif Maulidhan; Dihan, Fereshti Nurdiana (Majapahit Journal of Islamic Finance and Management, 2025)
This study aims to examine the influence of workplace facilities and work environment on employee involvement, with self-efficacy serving as a mediating variable, at PT. Saprotan Utama Semarang. The research is grounded in the notion that human resources play a vital role in enhancing organizational performance and competitiveness, where adequate facilities, a supportive work environment, and employees’ confidence in their abilities are key determinants. A quantitative approach was employed, using questionnaires as the data collection instrument, and data were analyzed through Structural Equation Modeling–Partial Least Square (SEM-PLS). The findings are expected to demonstrate that workplace facilities and work environment significantly affect both self-efficacy and involvement, while self-efficacy mediates the relationship between them. Practically, this research offers recommendations for companies to foster higher employee involvement by improving workplace facilities, creating a conducive environment, and strengthening employees’ self-efficacy to achieve optimal productivity.